IMPLEMENTATION OF CHARACTER EDUCATION IN THE MERDEKA CURRICULUM - Fauzi Irnawanto; Erna Yayuk; Kuncahyono Kuncahyono (Jurnal Eduscience)
Purpose-This study aims to examine the implementation of character education in the Merdeka Curriculum, focusing on planning, implementation, and evaluation in vocational school environments. This study is motivated by the decline in morals of the younger generation, which is marked by increasing juvenile delinquency, lack of discipline, and increasing social challenges in the digital era.